2013
DOI: 10.1161/circheartfailure.112.969717
|View full text |Cite
|
Sign up to set email alerts
|

Treating Anemia in Older Adults With Heart Failure With a Preserved Ejection Fraction With Epoetin Alfa

Abstract: Background Anemia is a common co-morbidity in older adults with heart failure and a preserved ejection fraction (HFPEF) and is associated with worse outcomes. We hypothesized that treating anemia with subcutaneous epoetin alfa (ESA) would be associated with reverse ventricular remodeling and improved exercise capacity and health status compared with placebo. Methods and Results Prospective, randomized, single blind, 24-week study with blinded endpoint assessment among anemic (average hemoglobin of 10.4±1 g/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 53 publications
1
39
0
Order By: Relevance
“…Evidence for improved outcomes after IV iron therapy is lacking. Small-scale studies treating HFpEF patients with erythropoietin-stimulating agents or oral iron reported no effect on left ventricular end-diastolic volume and left ventricular mass and no improvement in the submaximal exercise capacity or QoL [30, 31]. These findings are consistent with a report from Kasner et al [32], who did not find an association between functional iron deficiency and exercise capacity in patients with HFpEF.…”
Section: Iron In Diastolic Hfsupporting
confidence: 85%
“…Evidence for improved outcomes after IV iron therapy is lacking. Small-scale studies treating HFpEF patients with erythropoietin-stimulating agents or oral iron reported no effect on left ventricular end-diastolic volume and left ventricular mass and no improvement in the submaximal exercise capacity or QoL [30, 31]. These findings are consistent with a report from Kasner et al [32], who did not find an association between functional iron deficiency and exercise capacity in patients with HFpEF.…”
Section: Iron In Diastolic Hfsupporting
confidence: 85%
“…The severity of anaemia predicts mortality, but the role of treatment is uncertain. 42 As described above, peripheral endothelial dysfunction has been reported in HFpEF, 27 and might impair dynamic flow-mediated dilatation responses during exercise while also impairing matching of perfusion to regional demand in skeletal muscle microcirculation. 35,123 Combined cardiovascular reserve limitation Clearly, HFpEF is not simply caused by one pathophysiological factor, but in fact is a complex, highly-integrated, multisystem loss of cardiac and vascular reserve capacity -affecting the left and right ventricles, diastolic and systolic function, atrial reserve, heart rate and rhythm, autonomic control, the vasculature and microcirculation, and the periphery (Figure 3).…”
Section: Vascular Stiffening and Dysfunctionmentioning
confidence: 92%
“…Although these findings are inconclusive, treatment of anemia may be of benefit in some HFpEF patients. 47 …”
Section: Discussionmentioning
confidence: 99%